2013
DOI: 10.1128/aem.02523-12
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Residue Affecting Fatty Alcohol Selectivity in Wax Ester Synthase

Abstract: The terminal enzyme in the bacterial wax ester biosynthetic pathway is the bifunctional wax ester synthase/acyl-coenzyme A:diacylglycerol acyltransferase (WS/DGAT), which utilizes a fatty alcohol and a fatty acyl-coenzyme A (CoA) to synthesize the corresponding wax ester. In this report, we identify a specific residue in WS/DGAT enzymes obtained from Marinobacter aquaeolei VT8 and Acinetobacter baylyi that alters fatty alcohol selectivity and kinetic parameters when modified to alternative residues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(68 citation statements)
references
References 21 publications
3
63
2
Order By: Relevance
“…However, actinobacterial WS/DGAT paralogs are dispersed along the bacterial clusters (53). It was recently found that there are differences in the substrate selectivities of two different R. jostii WS/DGAT enzymes (50). The finding of these different paralogs in actinobacteria could be due to differences in enzyme selectivity.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…However, actinobacterial WS/DGAT paralogs are dispersed along the bacterial clusters (53). It was recently found that there are differences in the substrate selectivities of two different R. jostii WS/DGAT enzymes (50). The finding of these different paralogs in actinobacteria could be due to differences in enzyme selectivity.…”
Section: Discussionmentioning
confidence: 89%
“…Four hundred fifty-eight residues (97%) of Ma2 could be modeled at Ͼ90% accuracy, although the sequence identity between Ma2 and 2JPG is only 11%. The structural homology between Ma1 and 1Q9J was also recently reported (50).…”
Section: Structural Modeling Of Ws/dgat Proteins Predicts the Coadepementioning
confidence: 98%
“…Another very interesting finding concerning Ma1 from M. aquaeolei was the identification of the small alanine residue at position 360 to be relevant for the fatty alcohol chain length selectivity of Ma1 (89). The replacement of alanine by isoleucine resulted in an increased activity with the shorter-chain-length fatty alcohols nonanol and decanol compared to that of the wild-type enzyme, which is most active with dodecanol.…”
Section: Other Atfa-like Acyltransferases In Different Bacteriamentioning
confidence: 99%
“…Apart from that, the ratio of enzyme activities with hexadecanol versus dodecanol remained uninfluenced by the mutations. Therefore, the authors assumed that the incorporation of a larger amino acid residue does not block the access for longer-chain-length alcohols but improves the binding of shorter alcohols to the active site instead (89). The identification of residues affecting the substrate specificities of AtfA-like WS/DGATs is of great relevance for potential biotechnological utilization; hence, this recent study marks a first and important step in this direction.…”
Section: Other Atfa-like Acyltransferases In Different Bacteriamentioning
confidence: 99%
“…2.6‐ or 1.8‐fold higher when compared to the wild‐type AtfA, respectively. Ma1(A360I) showed a significant decrease in its activity toward n‐hexadecanol and n‐dodecanol, whereas the activity with nonanol was even 5.4‐fold higher when compared to the activity of the non‐mutated Ma1 enzyme . Although activities toward alcohols shorter than nonanol were not described in the latter publication, both enzyme variants seemed to be interesting enzymes for our study.…”
Section: Introductionmentioning
confidence: 76%